The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jsat.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Treating Tobacco Use Disorder in Pregnant Women in Medication-Assisted Treatment for an Opioid Use Disorder: A Systematic Review

Abstract: Smoking is associated with adverse effects on pregnancy and fetal development, yet 85-90% of pregnant women in medication-assisted treatment for an opioid use disorder smoke cigarettes. This review summarizes existing knowledge about smoking cessation treatments for pregnant women on buprenorphine or methadone, the two forms of medication-assisted treatment for opioid use disorder indicated for prenatal use. We performed a systematic review of the literature using indexed terms and key words to capture the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 91 publications
1
48
0
Order By: Relevance
“…A recent review of the literature identified only three interventions testing smoking cessation interventions among pregnant patients enrolled in MAT. 14 Contingency management (an incentive driven program) had an impact on smoking cessation. 25 More research is needed to develop and test tailored tobacco treatment interventions for pregnant, opioid dependent women for implementation in clinics providing MAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the literature identified only three interventions testing smoking cessation interventions among pregnant patients enrolled in MAT. 14 Contingency management (an incentive driven program) had an impact on smoking cessation. 25 More research is needed to develop and test tailored tobacco treatment interventions for pregnant, opioid dependent women for implementation in clinics providing MAT.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pregnant patients seeking MAT have high rates of smoking, ranging from 88% to 95%. 13,14 A significant risk of MAT is the development of neonatal abstinence syndrome, a treatable condition characterized by central and autonomic nervous system hyperactivity. 11 Babies who develop neonatal abstinence syndrome may require longer hospital stays 15 or neonatal intensive care unit (NICU) admissions.…”
Section: Smoking Among Pregnant Women In Outpatient Treatment For Opimentioning
confidence: 99%
“…First, participants were pregnant women receiving methadone-assisted treatment for opioid use disorder, a population with a high rate of smoking and for whom many interventions are ineffective (Akerman et al, 2015). Second, participants provided breath and urine samples three times per week throughout the study.…”
Section: Resultsmentioning
confidence: 99%
“…While typically used as an adjunct to treatment, contingency management has been shown to improve access and retention in treatment with pregnant women with substance use disorders in a limited number of studies (Akerman et al, 2015; Jones, Haug, Silverman, Stitzer, & Svikis, 2001). …”
Section: Literature Review and Discussionmentioning
confidence: 99%